1986
DOI: 10.1002/eji.1830161220
|View full text |Cite
|
Sign up to set email alerts
|

Use of Vpß.8 genes in splenic Lyt‐2+ cytotoxic lymphocyte precursors reactive to bm1 or bm14 alloantigen in individual C57BL/6 mice

Abstract: The cytotoxic response of cell sorter-purified small Lyt-2+ splenic cytotoxic lymphocyte precursors from 10 individual C57BL/6 mice to mutant class I H-2Kbm1 or H-2Dbm14 allodeterminants was analyzed under limiting dilution conditions. The cytotoxic activity of anti-bm1-specific or anti-bm14-specific cytotoxic T lymphocyte (CTL) populations (selected for a high probability of clonality) was tested against F23 hybridoma cells; F23+ CTL clones lysed F23 hybridoma targets but F23- CTL clones did not. In the C57BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1989
1989
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…Conversely, occurrence of Vb2.1 in the MLR-activated T cells was lower than that in the anti-CD3-activated T cells. We did not observe any extensive skewing toward particular single Vb genes reported in the allogeneic response toward HLA-DRw14 [14], H-2K bm1 and H-2D bm1 4 [15].…”
Section: Gene Occurrencecontrasting
confidence: 53%
“…Conversely, occurrence of Vb2.1 in the MLR-activated T cells was lower than that in the anti-CD3-activated T cells. We did not observe any extensive skewing toward particular single Vb genes reported in the allogeneic response toward HLA-DRw14 [14], H-2K bm1 and H-2D bm1 4 [15].…”
Section: Gene Occurrencecontrasting
confidence: 53%
“…This is, to our knowledge, the first structural analysis of rearranged TCR genes among human T cell clones in specific responses. Skewed V segment use among alloreactive T cells has also been observed in the mouse (25,(37)(38)(39), but very few V gene sequences were reported in these studies (25).…”
Section: Discussionmentioning
confidence: 95%
“…While no single Va or V0 gene can explain the high frequency of I-Aó`" 12 -reactive T cells in B10 mice, the frequency of expression of VP genes in I-Ab m12 -reactive T cells does not simply reflect the random usage of V0 genes . Reimann and Bellan (48) have studied the use of the V08 family of TCR 0 chains in the response to the mutant class I alloantigens K b-' and Kbm14. Using F23.1, which recognizes the Vß8.1, 8.2, and 8.3 0 chain domains, to study CTL clones generated from 136 mice and reactive with Kbml or Kbm14, they found that 37°jo of Kbm'-reactive CTL clones and 51% of Kbm14 -reactive CTL clones express Vß8-encoded TCRs .…”
Section: Discussionmentioning
confidence: 99%